More than just a stone a study on monuments and memorials in Iloilo City - Vargas, Hyacinth Mae P.
This research catalogue categorized all monuments and memorials with Iloilo City and determine whether they are public or privately instituted. It records and explains the current status of monuments and memorials inclusive on the districts of Arevalo, City Proper, La Paz, Lapuz, Mandurriao, and Molo. The researchers analyzed and assessed the management schemes and preservation efforts of the public and private sectors on their respective instituted monuments and memorials using the principal-agent theory. The researchers found out that private instituted monuments and memorials were better maintained and preserved than public instituted monuments and memorials. How the memorials and monuments look now, they reflect on how unimportant they are to the people and City of Iloilo. This research also recommends possible restoration and preservation efforts for all the neglected and dilapidated monuments and memorials.